Cor e ensino superior : trajetórias e experiências de estudantes cotistas da Universidade do Estado de Mato Grosso – UNEMAT - Costa, Jacqueline da Silva (2015)
This work was a study about students experiences and trajectories that entered at UNEMAT (Universidade do Estado do Mato Grosso) through PIIER (Programa de Integração e Inclusão Étnico-Racial). To achieve the goals aimed, it was risen information about: graduate quota students, active and dropout quota students, students who entered University by means of broad competition system, the meaning of the University, the reception of quota students, the relationship among quota students, non-quota students and professors from the perspective of policies adopted by UNEMAT, the mutual recognition and perception of identity construction and knowledge production. A comparative study of cases between two campi (Cáceres e Sinop) was adopted to concretize the research objectives. Documentary research, Survey and Qualitative Research were also done. The quantitative research (sample survey) and the qualitative research (in-depth interviews) reached 506 people. The results showed PIIER as an affirmative action program which has promoted equality, social justice and diversity at UNEMAT. It has positively impacted students life project reformulations. The presence of young or adult black students has pointed out that, while an historically racialized and marginalized group according to epistemological and cognitive justice point of view, they can instigate a set of cultural interrogations and challenges to the knowledge production which ones the university will have to deal with it.